Peran Kesiapan Berwirausaha dalam Memediasi Pengaruh Praktik Kewirausahaan terhadap Minat Berwirausaha Siswa SMK - Khansa Labibah; Dedi Purwana; Maulana Amirul Adha (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the mediating role of entrepreneurial readiness in the relationship between entrepreneurial practice and entrepreneurial interest among students of SMK Negeri 3 Jakarta. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The population consisted of students from grade X, XI, and XII of the Office Administration and Business Services program, with 118 students selected through proportionate stratified random sampling. Data were collected via Likert-scale questionnaires. Results indicate that: (1) entrepreneurial practice positively and significantly affects entrepreneurial readiness (β = 0.661; p = 0.000); (2) entrepreneurial practice does not directly and significantly affect entrepreneurial interest (β = 0.204; p = 0.059); (3) entrepreneurial readiness positively and significantly affects entrepreneurial interest (β = 0.594; p = 0.000); and (4) entrepreneurial practice positively and significantly affects entrepreneurial interest through entrepreneurial readiness as a full mediator (β = 0.392; p = 0.000). These findings suggest that increasing students' entrepreneurial interest cannot occur directly through practice alone, but requires that practical experience first be internalized into personal readiness.